2010
DOI: 10.1111/j.1467-9922.2009.00552.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonnative Processing of Verbal Morphology: In Search of Regularity

Abstract: There is little agreement on the mechanisms involved in second language (L2) processing of regular and irregular inflectional morphology and on the exact role of age, amount, and type of exposure to L2 resulting in differences in L2 input and use. The article contributes to the ongoing debates by reporting the results of two experiments on Russian verb generation and recognition in a lexical decision task (LDT) with priming by highly proficient late L2 learners, early interrupted (heritage) learners, and adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 46 publications
4
50
0
Order By: Relevance
“…Orsolini et al (1998) reported more overapplication errors for irregular than for regular verbs forms in Italian children's production of past tense and past participle formation, which they interpreted as evidence against the view that children's overgeneralization errors largely rely on regular (and only rarely on irregular) morphological processes (Marcus et al 1992). Gor & Cook (2010) investigated what they called regular, semi-regular, and irregular types of Russian verb forms in an auditory lexical decision task and obtained parallel effects across the three conditions, which they took to be "inconsistent with either the dual-system or the single-system approach to morphological processing" (Gor & Cook 2010: 88) which would have predicted stronger effects for regular than for irregular forms. The relevant typological insight here is that -in addition to word formation (viz.…”
Section: Stems and Inflectional Classesmentioning
confidence: 99%
“…Orsolini et al (1998) reported more overapplication errors for irregular than for regular verbs forms in Italian children's production of past tense and past participle formation, which they interpreted as evidence against the view that children's overgeneralization errors largely rely on regular (and only rarely on irregular) morphological processes (Marcus et al 1992). Gor & Cook (2010) investigated what they called regular, semi-regular, and irregular types of Russian verb forms in an auditory lexical decision task and obtained parallel effects across the three conditions, which they took to be "inconsistent with either the dual-system or the single-system approach to morphological processing" (Gor & Cook 2010: 88) which would have predicted stronger effects for regular than for irregular forms. The relevant typological insight here is that -in addition to word formation (viz.…”
Section: Stems and Inflectional Classesmentioning
confidence: 99%
“…This lesson served the dual purpose of exposing students to target-like evidence of manner/path combinations, as well as to extend their range of manner verbs (Gor & Cook, 2010). 14 specific manner-of-motion verbs were selected and taught in this session so that students would have resources beyond the basic swim, jump, and run which dominated preintervention writing samples (please see Appendix A for a list of manner-of-motion verbs taught in this lesson).…”
Section: Methodsmentioning
confidence: 99%
“…Classes met three days a week for three hours per session with approximately 1.5 hours of instruction dedicated to motion-event expression. The concepts of explicit instruction and explanation (Gor & Cook, 2010), negative evidence (Izumi & Lakshmanan, 1998;Strapp, Helmik, Tonkovich, & Bleakney, 2011), and specific aspects of the Conceptual Approach (White, 2012) were incorporated into the instructional design. Prior to the start of the intervention, the instructor informed the students that they would be engaged in activities designed to increase their awareness of English motion-event expression.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, L2 learners of German showed higher proficiency in the recognition of correct irregular verb participles as compared to regular verb participles. This difference might be the result of varying levels of processing automatization with lower levels in regular words and higher levels in irregular words in the L2 learners; potentially a result of formal instruction when learning regular and irregular verbs in German as L2 (Gor & Cook, 2010). As we selected L2 learners of German who had been residing in Germany for at least five years we expected to include a sample of learners with high competence in German (Birdsong, 2004).…”
mentioning
confidence: 99%